Pemetaan Pola Aliran Air Tanah Berbasis Sistem Informasi Geografis (SIG) Di Kawasan Kecamatan Tampan Kota Pekanbaru - Saldanela Saldanela; Sigit Sutikno; Andy Hendri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Tampan regency a districts in Pekanbaru city that is currently growing. Most of the population in the district use ground water for daily need. To observe such condition , mapping of ground water is conducted on the area. This research was intended to identify ground water flow and the availability of ground water in the area of Tampan district in Pekanbaru using Geographic information System (GIS). Survey and measurement is conducted during dry season. The output of the measurement are the coordinate and the elevation of the ground water. Dataprocessing is conducted using GIS based program that yields ground water contour which has been interpolated using Triangulated Irregular Network (TIN) and Inverse Distance Weighted (IDW) method. The drawing for ground water pattern is conducted by determining perpendicular line with the elevation contour of the ground water. Generally, some part of theground water flowing direction heads into the system and some other parts heads outside of the system (Tampan district). Ground water potential in this area is considered to be available of ground water comes from rain and the ground water itself.Keywords: GIS, TIN, IDW, ground water pattern, availability of ground water.